STUDIES ON FUNCTIONAL BACTERIA OF INDONESIAN TROPICAL FOREST PLANTS FOR BIOREHABILITATION OF DEGRADED LANDS - Irnayuli R. Sitepu; Yasuyuki Hashidoko; Aryanto Aryanto; Maman Turjaman; Satoshi Tahara; Siti S. Miftahuliyah; Erdy Santoso (Indonesian Journal of Forestry Research, 2008)
Forest  degradations  have left vast amount  of damaged  and abandoned  lands in Indonesia.   In this paper, we present our approaches  in rehabilitation of adverse soils using functional  bacteria isolated from plant species of Indonesian tropical  rain forests. For these purposes,  we collected  bacteria  from various  bio-geo-climatically different forests and conducted bioassays to test these bacterial abilities in improving plant growth. Repeated seedling-based studies on Shorea spp., Alstonia scholaris, Acacia crassicarpa, and Agathis lorantifolia have revealed that many bacteria were able to promote plant growth at early stage in the nursery.  Various  plant responses towards  inoculations suggested that although  forest soils maintain  highly diverse and potent  bacteria,  it is necessary to select appropriate approaches to obtain optimum  benefits from these plant-bacteria interactions.  Our  ideas and futures  studies  for further  management  of these plant- bacteria interactions for biorehabilitation are also discussed.